Antimicrobial stewardship program in a Greek hospital: implementing a mandatory prescription form and prospective audits. (17th April 2018) - Pitiriga, Vassiliki; Kanellopoulos, Petros; Kampos, Elsa; Panagiotakopoulos, George; Tsakris, Athanasios; Saroglou, George
Aim: Antimicrobial stewardship programs (ASPs) are urgently needed for Greek hospitals in order to improve antibiotic usage.Patients & methods: An ASP was implemented to a Greek hospital since February 2014. A mandatory order form was introduced for five antimicrobials; colistin, tigecycline, daptomycin, doripenem and linezolid. Prospective audits allowed for feedback to the prescribers without direct prescribing restriction.Results: Antimicrobials' consumption at the baseline year and the 3 years of ASP implementation was 93.7, 99.1, 156.1 and 105.9 defined daily doses/1000 patient days, respectively (p > 0.05). No statistically significant difference in isolation rates of multidrug-resistant pathogens was detected.Conclusion: Efforts are required to demonstrate the long-term impact of our program on antibiotic prescription attitudes as well as antimicrobial resistance rates.